Effectiveness of the Scramble Learning Model on Students' Ability to Understand Mathematical Concepts - Aprilia, Dian; Kintoko, Kintoko; Siswanto, Deny Hadi (Contemporary Education and Community Engagement (CECE), 2025)
This study aims to analyze the effectiveness of the use of the Scramble type cooperative learning model on the mathematical concept understanding ability of class VII students of Muhammadiyah 1 Mlati Junior High School: A Quasi-experimental Study with a Posttest Only Control Design consisting of two groups, namely the experimental class treated with the Scramble learning model (VII-B with 30 students) and the control class using conventional learning (VII-C with 30 students). The results of this study indicate that the sig. 2-tailed 0.000 < 0.05, which indicates a significant effect of the application of the Scramble model on the understanding of mathematical concepts. This study provides an important contribution to the development of more innovative mathematics teaching methods, where the implementation of learning from the teacher's side is quite high, namely 97.91% with an excellent category, while the implementation of learning by students reaches 96.15% with an excellent category.